Pengaruh Kualitas Makanan dan Pelayanan Karyawan terhadap Kepuasan Tamu Breakfast di Hotel Pangeran City Padang (International Forum of Researchers and Lecturers, 2024)
This research is motivated by several problems. The aim of this research is to analyze the influence of food quality and employee service on guest satisfaction at the Pangeran City Padang Hotel. The type of research used in this research is descriptive with quantitative data. The type of data used in this research is primary data. The population of this research is research conducted on guests staying at the Pangeran City Padang Hotel. Questionnaires were distributed to 88 research respondents. With a sampling technique using nonprobability sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this study show that the overall food quality variable is included in the adequate category at 55.68%. Overall employee service is included in the adequate category at 44.32%. Overall guest satisfaction is included in the less satisfied category at 40.60%. The influence of food quality and employee service on guest satisfaction with customized R Square is 51.3% while 48.7% is influenced by other factors.